Rules are essential, but they do not guarantee a win - Glassman, Saly A., 1958- (FT Press Delivers elements., 2011)
"This Element is an excerpt from It's about more than the money: investment wisdom for building a better life (ISBN: 9780137050321) by Saly A. Glassman. Get beyond frustration and anger, learn today's rules for investing more successfully, and get back into the game."--Resource description page.